Clinical outcome and prognosis of patients with acute myeloid leukemia submitted to chemotherapy with 5 years of follow-up - Kaira Mara Cordeiro de Albuquerque, M.Sc; Caroline Brandão Joventino; Lia Correia Moreira; Hermano Alexandre Lima Rocha, PhD; Lívia Andrade Gurgel; Deivide de Sousa Oliveira; Carlos Ewerton Maia Rodrigues, PhD (Hematology, Transfusion and Cell Therapy, 2024)
Objective: The purpose of this study was to evaluate the clinical-epidemiological profile, associated risk factors and clinical outcomes of patients with acute myeloid leukemia (AML), identifying the main causes of morbidity and mortality and overall survival rate of patients at five years of follow-up. Method: This was a retrospective cohort study evaluating the prognosis and clinical outcomes of 222 patients diagnosed with AML at three large hematology centers in Ceará (northeastern Brazil) over a period of five years. Results: The mean age at diagnosis was 44.1 ± 16 years, with a female prevalence of 1.3:1. No additional relevant risk factors associated with the development of AML were found, except for the well-established cytogenetic assessment. The overall 5-year survival rate was 39.4% (95%CI: 35.47 - 42.17). The main causes of death were disease progression (37.72%; n = 84) and sepsis (31.58%; n = 70). Conclusion: The clinical outcomes in our sample of AML patients were similar to those of other reported groups. Disease progression and infection were the main causes of death. Access to diagnostic flow cytometry and karyotyping was greater in our sample than in the national average. As expected, overall survival differed significantly according to the risk, as determined by cytogenetic testing.